Urgensi Partisipasi Masyarakat Sebagai Wujud Asas Keterbukaan Dalam Pembentukan Undang-Undang Nomor 17 Tahun 2022 Tentang Provinsi Sumatera Barat - Febrianda, lis (Jurnal Legislasi Indonesia, 2025)
Community participation is an embodiment of the principle of openness in the formation of laws and regulations, including in the formation of the Act Number 17 of 2022 concerning West Sumatra Province. Normatively, community participation is regulated in Article 5 and Article 96 of the Law concerning the Establishment of Legislative Regulations. Problem formulation (1) Has the concept of meaningful participation been implemented in the formation of the Act Number 17 of 2022? (2) What is the urgency of community participation as a manifestation of the principle of openness in the formation of the Act Number 17 of 2022? This research includes normative juridical research using a statutory approach and a conceptual approach using secondary data and analyzed using legal reasoning. Conclusions (1) The concept of meaningful participation was not implemented in the formation of the Act Number 17 of 2022 seriously (2) Community participation in the formation of the Act Number 17 of 2022 is very urgent. Without community participation, it is impossible for this law to be implemented properly